2017
DOI: 10.3390/diagnostics7010012
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Ovarian Cancer and Ovarian Cancer Screening

Abstract: Ovarian cancer is the foremost cause of gynecological cancer death in the developed world, as it is usually diagnosed at an advanced stage. In this paper we discuss current issues, the efficacy and problems associated with ovarian cancer screening, and compare the characteristics of ovarian cancer subtypes. There are two types of ovarian cancer: Type I carcinomas, which are slow-growing, indolent neoplasms thought to arise from a precursor lesion, which are relatively common in Asia; and Type II carcinomas, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 55 publications
1
74
0
5
Order By: Relevance
“…35 De novo breast and ovarian cancer metastases are also diagnosed at an early stage, before primary diagnosis. 12,13 Thus, to understand the metastatic behavior of breast and ovarian cancers, STRING analysis of upregulated proteins, known to be involved in controlling cell motility, was performed to uncover potential interactions that would regulate their downstream function in promoting metastasis, for instance, cell motility-related proteins such as coronin-1A (CORO-1A), a member of the WD repeat protein family, known to regulate cell signaling and cell migration. 36 In CAB patients, indirect interaction of CORO-1A with Rac1 through ARCT3 ( Figure 5A) has been known to regulate Rac1 associated functions such as cell migration and invasion in multiple cancers, as well as in activation of c-Jun N-terminal kinase (JNK) and JNK-dependent cell motility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 De novo breast and ovarian cancer metastases are also diagnosed at an early stage, before primary diagnosis. 12,13 Thus, to understand the metastatic behavior of breast and ovarian cancers, STRING analysis of upregulated proteins, known to be involved in controlling cell motility, was performed to uncover potential interactions that would regulate their downstream function in promoting metastasis, for instance, cell motility-related proteins such as coronin-1A (CORO-1A), a member of the WD repeat protein family, known to regulate cell signaling and cell migration. 36 In CAB patients, indirect interaction of CORO-1A with Rac1 through ARCT3 ( Figure 5A) has been known to regulate Rac1 associated functions such as cell migration and invasion in multiple cancers, as well as in activation of c-Jun N-terminal kinase (JNK) and JNK-dependent cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, depending on the breast cancer molecular subtype, it can spread to different organs such as bones, brain, lungs, and the liver. 12,13 Although breast and ovarian cancers are clinically distinct, mutations in tumor suppressor genes (BRCA1/2, p53, and PTEN) and proto-oncogenes, and changes in hormone regulation and microenvironment, indicate the similarities between breast and ovarian cancer. 11 However, de novo breast and ovarian cancer metastases, which could depend on the intrinsic properties of both malignant cells and microenvironment of metastasis-susceptible organ, has also been reported in some cases before the primary diagnosis of cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian cancer (OVC) is the second most common cause of mortality of female reproductive malignancies . In China, the incidence rate of OVC has raised over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer (OVC) is the second most common cause of mortality of female reproductive malignancies. [1][2][3] In China, the incidence rate of OVC has raised over the past decade. It has been reported that over 50 000 new cases were diagnosed and approximately 20 000 deaths were caused by OVC in 2015.…”
Section: Introductionmentioning
confidence: 99%